Dietary protein safety and resistance exercise: what do we really know? - Lowery, L. M.; Devia, L. (Journal of the International Society of Sports Nutrition, 2009)
Resistance trainers continue to receive mixed messages about the safety of purposely seeking ample dietary protein in their quest for stimulating protein synthesis, improving performance, or maintaining health. Despite protein`s lay popularity and the routinely high intakes exhibited by strength athletes, liberal and purposeful protein consumption is often maligned by "experts". University textbooks, instructors, and various forms of literature from personal training groups and athletic organizations continue to use dissuasive language surrounding dietary protein. Due to the widely known health benefits of dietary protein and a growing body of evidence on its safety profile, this is unfortunate. In response, researchers have critiqued unfounded educational messages. As a recent summarizing example, the International Society of Sports Nutrition (ISSN) Position Stand: Protein and Exercise reviewed general literature on renal and bone health. The concluding remark that"Concerns that protein intake within this range [1.4 - 2.0 g/kg body weight per day] is unhealthy are unfounded in healthy, exercising individuals." was based largely upon data from non-athletes due to "a lack of scientific evidence". Future studies were deemed necessary. This assessment is not unique in the scientific literature. Investigators continue to cite controversy, debate, and the lack of direct evidence that allows it. This review discusses the few existing safety studies done specific to athletes and calls for protein research specific to resistance trainers. Population-specific, long term data will be necessary for effective education in dietetics textbooks and from sports governing bodies.